Height, its components, and coagulability among older Chinese: The Guangzhou biobank cohort study. Issue 5 (7th June 2014) - Zhong, Y.; Jiang, C.Q.; Cheng, K.K.; Zhang, W.S.; Liu, B.; Jin, Y.L.; Lam, T.H.; Leung, G.M.; Schooling, C.M.
<x xml:space="preserve">Abstract</x> Objectives The causal role of some cardiovascular risk factors, such as HDL cholesterol, has been increasingly challenged and attention is returning to all elements of Virchow's triad, i.e., hypercoagulability (including viscosity) as well as endothelial function and blood flow. We examined the life course origins of coagulability. Methods We used multivariable linear regression to assess whether childhood influences, proxied by height and its components, were associated with hematocrit (Hct), hemoglobin (HGB), and other hematological parameters in 28, 595 older Chinese adults (mean age = 61.8 years) from the Guangzhou Biobank Cohort Study. Results Adjusted for age, sex, and recruitment phase, leg length was negatively associated with platelets (PLT) (−0.83 × 109/l per centimeter (cm), 95% confidence interval (CI) −1.01 to −0.65). Sitting height and height were positively associated with Hct (0.05% per cm, 95% CI 0.04–0.07 for sitting height; 0.02% per cm, 95% CI 0.01–0.02 for height), HGB (0.21 g/l per cm, 95% CI 0.17–0.25; 0.07 g/l per cm, 95% CI 0.04–0.09) and negatively associated with PLT (−1.2 × 109/l per cm, 95% CI −1.4 to −1.0; −0.83 × 109/l per cm, 95% CI −0.95 to −0.70). Further adjustment for potential confounders did little to change the estimates. Conclusions For the first time we provide anthropometric evidence for the different roles of prepubertal and pubertal influences in relation to Hct and HGB. Whether factors that promote leg growth but reduce growth of sitting height may help to prevent cardiovascular events, via effects on hypercoagulability or viscosity, overall or in specific subgroups, remains to be determined. Am. J. Hum. Biol. 26:603–608, 2014. © 2014 Wiley Periodicals, Inc.